The Evaluation of Cultural Identity by the Preservation of the Historical Heritage of Saint George in Mondonico - Francesca Andrulli; Chiara Bonaiti; Alessia Silvetti (Iconarp International Journal of Architecture and Planning, 2017)
The knowledge of the location, history and current state of conservation of historic built landscape is the best way to warrant its protection. We can only pass on to the next generations what we know and recognize as worthy and representative of our memory, improving the quality of life. Conservation of the architectural heritage is an opportunity to increase the economic resources also: “the historic buildings are a resource because they can satisfy new uses, compatible with their exiting features, that brings income and social advantages” (Della Torre, 2010). The organizations for designers’ training have a main role to suggest the right approach to reuse historical buildings. We don’t have to adhere to the common practice of simple renovations, refurbishments that deeply distort the entity and the environment in which it has been for hundreds of years. The case study of Saint George in Mondonico, is an example of that phase of the conservation process that deals with a profound knowledge of all the features of the buildings with the aim to discover and display the value. We can understand and decide the minimal conservative restoration interventions thanks to material and state of conservation of the building’s surveys and the detailed analysis through historical research needed to identify the construction phases and the interactions with the surrounding territory. Only this way we can clearly understand and use the remaining potentialities of the building and its surrounding. The valorisation of its potentiality is fundamental for the awareness of the value of the historic heritage for the local community that produced the objects in the past, and that has the duty to protect the remains, although if not always in a conscious way.